Abdominal ultrasonography with color Doppler analysis in the assessment of ileal Crohn’s disease: comparison with magnetic resonance enterography - da Silva Moraes, Antonio Carlos (Intest Res, 2019)
BACKGROUND/AIMS: Consistently defining disease activity remains a critical challenge in the follow-up of patients with Crohn’s disease (CD). We investigated the potential applicability of abdominal ultrasonography with color Doppler (USCD) analysis for the detection of morphological alterations and inflammatory activity in CD. METHODS: Forty-three patients with CD ileitis/ileocolitis were evaluated using USCD analysis with measurements obtained on the terminal ileum and right colon. Sonographic parameters included wall thickening, stricture, hyperemia, presence of intra-abdominal mass, and fistulas. Patients were evaluated for the clinical activity (Harvey-Bradshaw Index [HBI]), fecal calprotectin (FC) and C-reactive protein (CRP). The USCD performance was assessed using magnetic resonance enterography (MRE) as a criterion standard. RESULTS: Most measurements obtained with USCD matched the data generated with MRE; however, the agreement improved in clinically active patients where sensitivity, positive predictive value, and accuracy were >80%, considering wall thickening and hyperemia. Complications such as intestinal wall thickening, stricture formation, and hyperemia, were detected in the USCD analysis with moderate agreement with MRE. The best agreement with the USCD analysis was obtained in regard to FC, where the sensitivity, positive predictive value, and accuracy were >70%. The overall performance of USCD was superior to that of HBI, FC and CRP levels, particularly when considering thickening, stricture, and hyperemia parameters. CONCLUSIONS: USCD represents a practical noninvasive and low-cost tool for evaluating patients with ileal or ileocolonic disease, particularly in clinically active CD. Therefore, USCD might become a useful asset in the follow-up of patients with CD.